a) -15-(-9+7) x (-4)+(-3+9-2) x (-10)
Răspunsuri la întrebare
Răspuns de
1
Răspuns:
-15-(-9+7) x (-4)+(-3+9-2) x (-10)=
-15-(-2)·(-4)+4·(-10)=
-15+2·(-4)+(-40)=
-15+(-8)+(-40)=
-15-8-40= -63
Răspuns de
1
Răspuns: - 63
Explicație pas cu pas:
- 15 - ( - 9 + 7 ) × ( - 4 ) + ( - 3 + 9 - 2) × ( - 10 ) =
- 15 - ( -2 ) × ( - 4 ) + ( - 3 + 9 - 2) × ( - 10 ) =
- 15 + 2 × ( - 4 ) + ( 6 - 2) × ( - 10 ) =
- 15 - 8 + 4 × ( - 10 ) =
- 15 - 8 - 40 =
- 23 - 40 =
- 63
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Ed. muzicală,
8 ani în urmă
Informatică,
9 ani în urmă